Association Between Periodontal Disease and Atherosclerotic Cardiovascular Diseases: Revisited - Zardawi, Faraedon; Gul, Sarhang; Abdulkareem, Ali; Sha, Aram; Yates, Julian (Frontiers in Cardiovascular Medicine, 2021)
Atherosclerotic cardiovascular disease (ACVD) is an abnormal narrowing of the coronary arteries associated with atheroma formation, which can cause disability and often death. Periodontitis is ranked as the sixth most prevalent disease affecting humans affecting 740 million people worldwide. In the last few decades, researchers have focused on the effect of periodontal disease (PD) on cardiovascular disease. The aim of this review was to investigate the strength of the association between these two diseases. PD is a potential risk factor that may initiate the development, maturation and instability of atheroma in the arteries. Two mechanisms were proposed to explain such association, either periodontal pathogens directly invade bloodstream or indirectly by increasing systemic level of inflammatory mediators. Interestingly, it has been suggested that improvement in the condition of one disease positively impact the condition of the other one. Highlighting the strength of association between these two diseases, the importance of early diagnosis and treatment of PD and its impact on cardiovascular status may be of great value in reducing the complications associated with ACVDs. Further in vitro and in vivo studies with longer follow up are necessary to confirm the causal relationship between PD and ACVDs.